2011
DOI: 10.1097/jgp.0b013e3181ff63be
|View full text |Cite
|
Sign up to set email alerts
|

Depressive Symptoms and Change in Abdominal Obesity in the Elderly: Positive or Negative Association?

Abstract: Objectives Recent evidence suggests depression could result in abdominal obesity in the elderly. Few longitudinal studies are available and none has been conducted outside of the US. Methods To examine the relationship between depressive symptoms and abdominal obesity, data from 3998 community dwelling Chinese elderly men and women aged 65 years and above with 4-year follow up were analyzed. Depression was defined by a Geriatric Depression Scale score of 8 or higher. At baseline and after 4 years, overall ob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 55 publications
(43 reference statements)
0
6
0
Order By: Relevance
“…In particular, Toker et al [ 18 ] proposed that depression may be positively associated with higher waist circumference and TG level among women. Similarly, depressive symptoms are associated with higher risk for abdominal obesity among women, but not among men, after controlling the covariates [ 19 , 26 ]. Among German population, depressive symptoms are significantly associated with higher waist circumference and dyslipidemia (lower HDL cholesterol) among women, but not among men, after covariate adjustment [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…In particular, Toker et al [ 18 ] proposed that depression may be positively associated with higher waist circumference and TG level among women. Similarly, depressive symptoms are associated with higher risk for abdominal obesity among women, but not among men, after controlling the covariates [ 19 , 26 ]. Among German population, depressive symptoms are significantly associated with higher waist circumference and dyslipidemia (lower HDL cholesterol) among women, but not among men, after covariate adjustment [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…This elevation in serum cortisol can increase abdominal fat deposition, promoting glucose intolerance and hypertension [ 16 , 17 ]. However, the lack of correlation between depression and visceral fat has been demonstrated in the elderly [ 18 ]. In contrast, we could demonstrate that the total amount of body fat may be more related to psychiatric symptoms than central fat per se .…”
Section: Discussionmentioning
confidence: 99%
“…However, a smaller study of African American adults ( n = 253; (ages 18 to 60 years old) reported a positive association between CES-D scores and WHR levels after controlling for socioeconomic confounders [10]. The more general literature on sex differences in the relations between depressed mood and WHR [14, 15, 2224] ranges from studies reporting unadjusted or modestly adjusted positive results in both men and women to studies reporting no association in either sex after accounting for confounders similar to the current study. However, the latter studies finding no associations in either sex were conducted in the Netherlands [24] and China [14] with samples of older adults.…”
Section: Discussionmentioning
confidence: 99%
“…While research on these sex differences is largely based on predominantly white samples in the USA [7, 8, 1620] and on samples in other countries [14, 15, 2133], several investigations in the USA have examined racially diverse samples that included substantial representation by African Americans [8, 3438]. However, this literature is limited by its dearth of research specifically investigating sex differences in African Americans, with the exception of two studies that found that depressive symptoms were not associated with blood pressure [8] or high-sensitivity C-reactive protein (hsCRP) [38] in either African American women or African American men.…”
Section: Introductionmentioning
confidence: 99%